Corynebacterium dentalis sp. nov., a new bacterium isolated from dental plaque of a woman with periodontitis. (January 2020) - Benabdelkader, S.; Boxberger, M.; Lo, C.I.; Aboudharam, G.; La Scola, B.; Fenollar, F.
Abstract: Strain Marseille-P4122 T is a new species from the order Corynebacteriales that was isolated from the dental plaque of a woman with periodontitis. It is a facultative anaerobic Gram-positive rod-shaped bacterium. Strain Marseille-P4122 T exhibited a 98.19% sequence identity with Corynebacterium suicordis strain P81/02, the phylogenetically closely related species with standing in nomenclature. The draft genome size of strain Marseille-P4122 T is 2.49 Mb with 60.1% G + C content. We propose that strain Marseille-P4122 T (=CSURP4122) is the type strain of the new species Corynebacterium dentalis sp. nov.